Réponses

2014-03-10T09:50:10+01:00
C1a
(2+ \sqrt{3}) ^{2}  =4+4 \sqrt{3}+3=7+4 \sqrt{3}
C2b
f(2+ \sqrt{3})= (2+ \sqrt{3})^{2}  -4(2+ \sqrt{3})+1
f(2+ \sqrt{3})=7+4 \sqrt{3}-8-4 \sqrt{3}+1=0
C2
(2- \sqrt{3} )^{2} =4-4 \sqrt{3}+3=7-4 \sqrt{3}
f(2- \sqrt{3})=7-4 \sqrt{3}-8+4 \sqrt{3}+1=0

D1
ax²+bx+c=x²-4x+1
Donc a=1, b=-4, c=1
D2
b²-4ac=(-4)²-4*1*1=16-4=12
D3
Les solutions sont :
 \frac{(-b+ \sqrt{b^{2}-4ac)}}{2a} = \frac{4+2 \sqrt{3} }{2} =2+ \sqrt{3}
et
 \frac{-b- \sqrt{ b^{2}-4ac}}{2a}= \frac{4-2 \sqrt{3}}{2}=2- \sqrt{3}